The Evolution of Research and Therapy With Hypomethylating Agents in Acute Myeloid Leukemia and Myelodysplastic Syndrome: New Directions for Old Drugs. Issue 1 (January 2022) - Short, Nicholas J.; Dombret, Hervé; Adès, Lionel; Kantarjian, Hagop
Abstract: Azacitidine and decitabine are cytosine analogs that function as DNA methyltransferase inhibitors. These agents, commonly referred to as "hypomethylating agents, " are widely used for the treatment of myelodysplastic syndrome and acute myeloid leukemia (AML). In this review, we discuss the clinical development of these drugs, including the early studies that led to the optimization of their doses and schedules, and the pivotal studies that led to their regulatory approval, both as monotherapy and in combination with venetoclax for older adults with AML who are unfit for intensive chemotherapy. We also review the more recent development of oral hypomethylating agent formulations and the novel oral strategies being developed in myelodysplastic syndrome and AML.